Lysophosphatidic acid as an initiator of neuropathic pain: biosynthesis and demyelination. (April 2011) - Ueda, Hiroshi; Ueda, Mutsumi
The injury-induced intense stimulation of spinal cord neurons causes lysophosphatidic acid (LPA) synthesis. LPA1 receptor activation causes demyelination and sprouting of sensory fibers, leading to an induction of synaptic reorganization underlying allodynia, a phenomenon that causes intense pain by innocuous stimuli such as touch. the LPA1 receptor signal also initiates the upregulation of Cav αα2δδ1 in dorsal root ganglia and PKC-γγ in the dorsal horn and the downregulation of substance P in the dorsal horn, which are underlying mechanisms for characteristic neuropathic hyperalgesia in myelinated sensory (A-type) fibers and unmyelinated sensory (C-type) fiber hypoesthesia (a type of sensory loss), respectively. On the other hand, the LPA3 receptor mediates microglia activation at the early stage after nerve injury and LPA-induced LPA biosynthesis. Thus, both LPA1 and LPA3 receptors play key roles in the initiation step for neuropathic pain.